Fungicide-Derived Copper Content in Soil and Vegetation Component, Owena Cocoa (Theobroma Cacao L.) Plantations in Nigeria (Bangladesh Journal of Scientific and Industrial Research, 2007)
This work reported the results of copper content in the soil profiles of three different aged cocoa plantations subjected to copper- fungicide application and the various vegetational components (pod, beans, leaves, trunk bark, lateral root and twig). Soil copper at various depth considered ranged from 5.0 -42.0 μgg-1. Copper contents in both fresh and dry leaves of cocoa and banana were consistently high in all the three plantations. The copper contents ranged from 56-300μgg-1 (dry wt.) in cocoa trunk bark and 86-161μgg-1 in banana trunk bark. There was evidence of age-dependent accumulation of copper in cocoa pod and beans; hence it can be used to assess the degree of copper contamination. Copper contents from roots ranged from 408-2, 203μgg-1 (dry wt.). The soil did not appear contaminated by copper but alternative fungicide is recommended since copper accumulation in the cocoa beans was evident.Bangladesh J. Sci. Ind. Res. 41(3-4), 129-140, 2006